Efficacy of fungicides in controlling botrytis gray mold of chickpea (Cicer arietinum L.) (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was carried out at Regional Pulses Research Station (RPRS), Madaripur during Rabi season of 2011-12 and 2012-13 to evaluate the most effective fungicides in controlling Botrytis Gray Mold (BGM) of Chickpea. Five different fungicides e.g. Propiconazole (Tilt 250 EC), Carbendazim (Bavistin DF), Fenamidone+Mancozeb (Secure 600 WG), Difenoconazole (Score 250 EC), Tebuconazole (Folicure 250 EC) were evaluated under natural condition. Results revealed that among the five fungicides Fenamidone+Mancozeb (Secure 600WG) sprayed at the rate of 1g/L with 7 days interval gave the lowest BGM score of 3.80 and 4.00 in 1-9 scale during 2011-12 and 2012-13 and produced highest yield of 1547 and 1443 kg/ha, respectively. Besides, the highest BGM was scored by the untreated control plot (6.26 and 6.33) and produced the lowest yield of 988 and 853 kg/ha during the two consecutive years.Bangladesh J. Agril. Res. 40(3): 391-398, September 2015